2020
DOI: 10.2298/botserb2001071y
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of the essential oil of Salvia bracteata banks and the biological activity of its extracts: Antioxidant, total phenolic, total flavonoid, antifungal and allelopathic effects

Abstract: The present study was conducted with the aim of determining biological activities of the Salvia bracteata plant, activities such as its antioxidant, total phenolic, total flavonoid, allelopathic and antifungal effects. To this end, aboveground parts (flowers + shoots + leaves) of S. bracteata plants were collected in the province of Kırşehir, Turkey, during the flowering stage in 2018. As a result of GC-MS analysis, 23 constituents were identified, representing 96.21% of the essential oil. The major compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Furthermore, it is known that linalyl acetate can reduce oxidative changes 75 . In addition, some species from genus Salvia such as S. limbata and S. bracteata have good antioxidant effects 7,76 . It is clear that EO compounds act synergistically, antagonistically and additively 77…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is known that linalyl acetate can reduce oxidative changes 75 . In addition, some species from genus Salvia such as S. limbata and S. bracteata have good antioxidant effects 7,76 . It is clear that EO compounds act synergistically, antagonistically and additively 77…”
Section: Resultsmentioning
confidence: 99%
“…The CUPRAC assay was performed according to the procedure described in [ 57 ]. A calibration curve was prepared using different concentrations of ascorbic acid as a standard, and results were expressed as milligrams of ascorbic acid equivalents (AAEs) per gram of DW.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported by Yilar et al (2020a) that S. absconditiflora species can grow in alkaline (pH 7.58-8.30), high CaCO3 (3.78-67.45%), medium organic matter (1.39-3.71%) and clay loam soils. In another study, Yilar et al (2020b) for salvia species water saturation 58.3%, pH 8.09, total salinity 0.008%, total calcerous ratio 14.074%, organic matter 3.501%, K2O 98.766 kg da -1 and P2O5 3.914 kg da -1 have obtained data. When examining Table 4, it was determined that the soil samples included the values between low (3.6±0.976 mg kg -1 ) and high (43.2±0.326 mg kg -1 ) in terms of available P and between low (120±2.836 mg kg -1 ) and high (398±5.672 mg kg -1 ) in terms of changeable K. It was observed that Salvia ceratophylla, S. bracteata, S. absconditiflora and S. aethiopis species can grow in soil with a low level of phosphorus.…”
Section: Resultsmentioning
confidence: 94%